Propagation velocity of a vibration velocity wave, i.e. acoustic velocity wave - WYRZYKOWSKI, Roman (Archives of Acoustics, 1987)
In this paper the author proves that the propagation velocity of an acoustic velocity wave in the near field differs from the velocity of a pressure wave, while both differ from c_0 in d'Alambert's equation. The velocity of an acoustic velocity wave was calculated for a point source, for a cylindrical source of zero order and for a circular piston and ring in a baffle.